ДО ПИТАННЯ НАВЧАННЯ ПАСИВНОЇ ЛЕКСИКИ МОЛОДШИМИ ШКОЛЬНИКАМИ (Педагогіка вищої та середньої школи, 2022)
The article deals with the using of passive grammar in the process of foreign teaching reading. The principles o f junior schoolmates passive lexic teaching are elaborated and the interaction between teacher and pupils during its studying is represented.